The Polish Institute of International Affairs: Its legal and financial issues - Jacek Wantoch-Rekowski (Prawo Budżetowe Państwa i Samorządu)
This article concerns the Polish Institute of International Affairs, which is a state legal person and counts as a unit of the public finance sector. It has a relatively long tradition, as it was established in 1947. The institute's tasks result mainly from the current Act on the institute and its statutes. In terms of financial issues, statutory regulations are sparse. An analysis of the institute's financial plans, contained in annexes to the budgetary acts, revealed that the entity can only function owing to a subjective subsidy from the state budget.